Open Access

Character sums over generalized Lehmer numbers

Journal of Inequalities and Applications20162016:270

https://doi.org/10.1186/s13660-016-1213-y

Received: 12 July 2016

Accepted: 14 October 2016

Published: 3 November 2016

Abstract

Let \(q>2\) be an integer, \(n\geqslant2\) be a fixed integer with \((n,q)=1\), ψ be a non-principal Dirichlet character modq. An upper bound estimate for character sums of the form
$$\sum_{a\in\textit{C}(1,q)}\psi(a) $$
is given, where \(\mathcal{C}(1,q)=\{a \mid 1\leqslant a\leqslant q-1, a\overline{a}\equiv1 (\bmod q), n\nmid(a+\overline{a})\}\).

Keywords

Lehmer numbercharacter sumsKloosterman sumsupper bound estimate

MSC

11L0511L4011N37

1 Introduction

Let q be an odd integer, c be a fixed positive integer with \((c,q)=1\). For each integer a with \(1\leqslant a\leqslant q-1\) and \((a,q)=1\), it is clear that there exists one and only one integer b with \(1\leqslant b\leqslant q-1\) such that \(ab\equiv c (\bmod q)\). If a and b are of opposite parity, then a is called a Lehmer number. Let \(\mathcal{A}(c,q)\) denote the set of all Lehmer numbers, and \(r(c,q)\) the number of \(\mathcal{A}(c,q)\). Lehmer [1] posed the problem of finding \(r(1,q)\).

Before proceeding we need to recall that the notations \(U = O(V)\) and \(U \ll V\) are equivalent to \(\vert U\vert \le c V\) for some constant \(c>0\). We write \(\ll_{\rho}\) and \(O_{\rho}\) to indicate that this constant may depend on the parameter ρ. \(\sum^{'}\) means summing over reduced residue classes, denotes the multiplicative inverse of a modulo q and for a real x we denote \(e(x)=e^{2\pi i x}\), \(\{x\}\) the fractal part of x, and \(\langle x\rangle=\min\{\{x\},1-\{x\}\}\).

In 1993, Zhang [2] proved that
$$\begin{aligned}& r \bigl(1,p^{\alpha} \bigr)=\frac{\phi(p^{\alpha})}{2}+O \bigl(p^{\alpha/2}\ln ^{3} \bigl(p^{\alpha} \bigr) \bigr), \\ & r(1,pl)=\frac{\phi(pl)}{2}+O \bigl((pl)^{1/2}\ln^{2}(pl) \bigr), \end{aligned}$$
where p, l are two distinct odd primes, α is a positive integer, and \(\phi(q)\) is the Euler function. For arbitrary odd integer \(q\ge3\), he [3] soon obtained
$$r(1,q)=\frac{\phi(q)}{2}+O \bigl(q^{1/2}d^{2}(q) \ln^{2}q \bigr), $$
where \(d(q)\) is the classical divisor function.
Later, Lu and Yi [4] generalized this problem to incomplete intervals. In fact, let \(q\ge3\) be an integer, \(n\geqslant2\) and c be two fixed integers with \((n,q)=(c,q)=1\), \(0<\delta_{1},\delta _{2}\leqslant1\), they defined
$$r_{n}(\delta_{1},\delta_{2},c;q)=\mathop{ \mathop{\mathop{{\sum }'}_{a\leqslant\delta_{1}q}\ \mathop{{\sum }'}_{b\leqslant\delta_{2}q}}_{ab\equiv c (\bmod q)}}_{n\nmid(a+b)}1, $$
and got an asymptotic formula as follows:
$$r_{n}(\delta_{1},\delta_{2},c;q)= \biggl(1- \frac{1}{n} \biggr)\delta _{1}\delta_{2}\phi(q) +O_{n} \bigl(q^{1/2}d^{6}(q)\log^{2}q \bigr). $$
Recently, interesting connections between Lehmer numbers and character sums were investigated by some scholars. For example, for an odd prime p, and a fixed prime w less than p, let
$$\mathcal{B}(w,p)= \bigl\{ a\mid 1\leqslant a\leqslant p-1, a\overline{a}\equiv1 ( \bmod p), a\equiv\overline{a} (\bmod w) \bigr\} . $$
Then, for any non-principal Dirichlet character \(\chi \bmod w\), Ma, Zhang and Zhang [5] got an upper bound estimate of character sums over \(\mathcal{B}(w,p)\) as
$$\mathop{\mathop{\sum}_{a=1}}_{a\in\mathcal{B}(w,p)}^{p-1}\chi (a)\ll_{w} p^{1/2+\epsilon}. $$
At almost the same time, Han and Zhang [6] obtained an upper bound estimate of the character sums over Lehmer numbers as
$$\begin{aligned} \sum_{a\in\mathcal{A}(1,p)}\chi (a)= \mathop{\mathop{ \sum }_{a=1}}_{2 \nmid(a+\overline {a})}^{p-1}\chi(a)\ll p^{1/2} \ln^{2}p, \end{aligned}$$
(1.1)
where χ is an arbitrary non-principal character modulo an odd prime p.

The results of character sums over other special numbers or polynomials can also be found in [7] and [8]. For more properties of character sums and their various applications, see [9, 10] and the references therein.

It seems that (1.1) cannot be extended to arbitrary integer q by their methods in [6]. However, relying on the methods in [4], we can overcome the obstacles.

Let \(q\ge3\) be an integer, \(n\geqslant2\) be a fixed integer with \((n,q)=1\), ψ be a non-principal Dirichlet character modulo q. If \(n\nmid (a+\overline{a})\), then a is called a generalized Lehmer number. Denote the set of all generalized Lehmer numbers by
$$\mathcal{C}(1,q)= \bigl\{ a \mid 1\leqslant a\leqslant q-1, a\overline{a}\equiv 1 (\bmod q), n\nmid(a+\overline{a}) \bigr\} . $$
Following the same technique as in [4], we obtain the following.

Theorem

Let \(q\ge3\) be an integer, \(n\geqslant2\) be a fixed integer with \((n,q)=1\), ψ be a non-principal Dirichlet character \(\bmod\ q\). Then we have the upper bound estimate
$$\sum_{a\in\mathcal{C}(1,q)}\psi(a)=\mathop{\mathop {{\sum }'}_{a=1}}_{n\nmid(a+\overline{a})}^{q}\psi(a) \ll_{n} q^{1/2}d^{5}(q)\log^{2}q. $$

Let \(q\ge3\) be an odd integer, \(n=2\) in the theorem, we may immediately obtain the following.

Corollary 1

Let ψ be a non-principal Dirichlet character modulo q. Then we have
$$\sum_{a\in\mathcal{A}(1, q)}\psi(a)=\mathop{\mathop {{\sum }'}_{a=1}}_{2\nmid(a+\overline{a})}^{q}\psi(a)\ll q^{1/2}d^{5}(q)\log^{2}q. $$

Let q be an odd prime p, \(n=2\) in Corollary 1, then (1.1) can be deduced directly as follows.

Corollary 2

Let ψ be a non-principal Dirichlet character modulo p. Then we have
$$\sum_{a\in\mathcal{A}(1, p)}\psi(a)\ll p^{1/2} \log^{2}p. $$

2 Some lemmas

To prove the theorem, we need the following several lemmas. First we need an upper bound estimate of the general Kloosterman sum \(S(m,n,\chi;q)\) as follows.

Lemma 1

Let q be a positive integer and χ a Dirichlet character \(\bmod\ q\). Then for any integers m and n, we have
$$S(m,n,\chi;q)\ll q^{1/2}(m,n,q)^{1/2}d(q), $$
where \(S(m,n,\chi;q)\) is defined by
$$S(m,n,\chi;q)=\sum_{a \bmod q}\chi(a)e \biggl( \frac {ma+n\overline{a}}{q} \biggr). $$

Proof

See Lemma 1 of [7]. □

Lemma 2

Let q be a positive integer, \(\chi_{0}\) be the principal Dirichlet character \(\bmod\ q\), ψ be a non-principal character modq, \(r_{1}\), \(r_{2}\) be integers with \(1\leqslant r_{1}, r_{2}\leqslant q-1\). Then we have
$$\bigl\vert G(r_{1},\psi)G(r_{2},\chi_{0}) \bigr\vert \leqslant q^{1/2}(r_{1},q) (r_{2},q). $$

Proof

By Lemma 2 of Chapter 1.2 in [11], we have
$$G(r_{2},\chi_{0})=\mu \biggl(\frac{q}{(r_{2},q)} \biggr) \phi(q)\phi ^{-1} \biggl(\frac{q}{(r_{2},q)} \biggr)\leqslant (r_{2},q), $$
where we have used the fact \(\phi(q)/\phi(t)\leqslant q/t\) if \(t \mid q\).

Note that ψ is a non-principal character \(\bmod\ q\), we only need to consider the following cases.

If \((r_{1},q)=1\), we have
$$\bigl\vert G(r_{1},\psi) \bigr\vert = \bigl\vert \overline{ \psi}(r_{1})G(1,\psi ) \bigr\vert = \bigl\vert G(1,\psi) \bigr\vert =q^{1/2}. $$
If \((r_{1},q)>1\), and ψ is a primitive character \(\bmod\ q\), we have
$$\bigl\vert G(r_{1},\psi) \bigr\vert = \bigl\vert \overline{ \psi}(r_{1})G(1,\psi ) \bigr\vert \le q^{1/2}. $$
If \((r_{1},q)>1\), and ψ is a non-primitive character \(\bmod\ q\), then Lemma 5 of Chapter 1.2 in [11] indicates that there exists one and only one \(q^{\ast} \) such that \(q^{\ast} \mid q\), with \(\chi^{\ast}\) the primitive character \(\bmod\ q^{\ast}\) corresponding χ. Thus
$$\begin{aligned} \bigl\vert G(r_{1},\psi) \bigr\vert \leqslant& \biggl\vert \overline{\chi }^{\ast} \biggl(\frac{r_{1}}{(r_{1},q)} \biggr) \chi^{\ast} \biggl(\frac{q}{q^{\ast}(r_{1},q)} \biggr)\mu \biggl(\frac{q}{q^{\ast}(r_{1},q)} \biggr) \phi(q)\phi^{-1} \biggl(\frac{q}{(r_{1},q)} \biggr)\tau \bigl( \chi^{\ast } \bigr) \biggr\vert \\ \leqslant &q^{1/2}(r_{1},q). \end{aligned}$$
Combining the above, we have
$$\bigl\vert G(r_{1},\psi)G(r_{2},\chi_{0}) \bigr\vert \leqslant q^{1/2}(r_{1},q) (r_{2},q). $$
 □

Lemma 3

Let \(q\ge3\) be an integer, χ, ψ be Dirichlet characters modq such that \(\psi\neq\chi_{0}\) and \(\psi\overline{\psi}=\chi_{0}\). Then we have the estimate
$$\mathop{\mathop{\sum_{\chi\bmod q}}_{\chi\neq\chi_{0}}}_{\chi \neq\overline{\psi}} G(r_{1},\chi\psi)G(r_{2},\chi)\ll\phi (q)q^{1/2}(r_{1},q)^{1/2}(r_{2},q)^{1/2}d(q). $$

Proof

Combining Lemmas 1 and 2, we have
$$\begin{aligned}& \mathop{\mathop{\sum_{\chi\bmod q}}_{\chi\neq \chi_{0}}}_{\chi\neq\overline{\psi}} G(r_{1},\chi\psi)G(r_{2},\chi) \\& \quad =\sum_{\chi\bmod q}G(r_{1},\chi \psi)G(r_{2},\chi) -G(r_{1},\psi)G(r_{2}, \chi_{0})-G(r_{1},\chi_{0})G(r_{2}, \overline {\psi}) \\& \quad =\sum_{\chi\bmod q}\sum_{a=1}^{q} \chi\psi (a)e \biggl(\frac{ar_{1}}{q} \biggr) \sum_{b=1}^{q} \chi(b)e \biggl( \frac{br_{2}}{q} \biggr) \\& \quad\quad{} -G(r_{1},\psi)G(r_{2},\chi_{0})-G(r_{1}, \chi _{0})G(r_{2},\overline{\psi}) \\& \quad =\phi(q) \mathop{{\sum}'}_{a=1}^{q} \psi(a) \mathop{\mathop{{\sum}'}_{b=1}}_{ab\equiv1 (\bmod q)}^{q}e \biggl(\frac{ar_{1}+br_{2}}{q} \biggr) \\& \quad =\phi(q)S(r_{1},r_{2},\psi;q) -G(r_{1}, \psi)G(r_{2},\chi _{0})-G(r_{1}, \chi_{0})G(r_{2},\overline{\psi}) \\& \quad \ll\phi (q)q^{1/2}(r_{1},r_{2},q)^{1/2}d(q)+q^{1/2}(r_{1},q) (r_{2},q) \\& \quad \ll\phi(q)q^{1/2}(r_{1},q)^{1/2}(r_{2},q)^{1/2}d(q). \end{aligned}$$
 □

Lemma 4

Let \(0<\rho\leqslant\frac{1}{2}\), \(x_{0},x_{1},\ldots, x_{k}\) be a sequence of real numbers such that
$$\langle x_{k}-x_{k'}\rangle \geqslant\rho,\quad\quad x_{k}\neq x_{k'}, $$
and \(\langle x_{0}\rangle =\min \{\langle x_{1}\rangle , \ldots, \langle x_{k}\rangle \}\). Then we have
$$\sum_{k=1}^{K}\frac{1}{\langle x_{k}\rangle }\ll \rho^{-1}\log(K+1). $$

Proof

See Lemma 2 of Chapter 5.1 in [11]. □

Lemma 5

Let \(q\ge3\) be an integer, ψ be a character \(\bmod \ q\), \(n\geqslant2\) be a fixed integer with \((n,q)=1\), l be an integer with \(1\leqslant l\leqslant n\). Then we have
$$\mathop{{\sum}'}_{a=1}^{q}\mathop{{ \sum}'}_{b=1}^{q}\psi(a) e \biggl( \frac{(a+b)l}{n} \biggr)\ll q^{1/2}\phi(q)d^{2}(q)\log q. $$

Proof

The relations
$$1\leqslant l\leqslant n, \quad\quad 1\leqslant r\leqslant q-1,\quad\quad (n,q)=1 $$
imply that
$$\frac{l}{n}-\frac{r}{q}\neq0. $$
And also
$$\psi(a)=\frac{1}{q}\sum_{r=1}^{q}G(r, \psi)e \biggl(-\frac{ar}{q} \biggr)= \frac{1}{q}\sum _{r=1}^{q-1}G(r,\psi)e \biggl(-\frac{ar}{q} \biggr). $$
Thus
$$\begin{aligned}& \mathop{{\sum}'}_{a=1}^{q}\mathop{{ \sum }'}_{b=1}^{q}\psi(a) e \biggl( \frac{(a+b)l}{n} \biggr) \\& \quad =\sum_{a=1}^{q}\psi(a)e \biggl( \frac{al}{n} \biggr) \mathop{{\sum}'}_{b=1}^{q}e \biggl(\frac{bl}{n} \biggr) \\& \quad =\sum_{a=1}^{q}\frac{1}{q} \sum _{r=1}^{q-1}G(r,\psi)e \biggl(- \frac{ar}{q} \biggr)e \biggl(\frac{al}{n} \biggr) \mathop{{\sum }'}_{b=1}^{q}e \biggl( \frac{bl}{n} \biggr) \\& \quad =\frac{1}{q}\sum_{r=1}^{q-1}G(r, \psi)\mathop{{\sum}'}_{b=1}^{q}e \biggl( \frac{bl}{n} \biggr) \sum_{a=1}^{q}e \biggl( \biggl(\frac{l}{n}-\frac{r}{q} \biggr)a \biggr) \\& \quad =\frac{1}{q}\mathop{{\sum}'}_{b=1}^{q}e \biggl(\frac{bl}{n} \biggr) \Biggl(\sum_{r=1}^{q-1} G(r,\psi)\frac{f(l,r,n,q)}{e (\frac{r}{q}-\frac{l}{n} )-1} \Biggr), \end{aligned}$$
where \(f(l,r,n,q)=1-e ( (\frac{l}{n}-\frac{r}{q} )q )\).
Apply the upper bound
$$\bigl\vert G(r,\psi) \bigr\vert \leqslant q^{1/2}(r,q), $$
we have
$$\begin{aligned} \sum_{r=1}^{q-1} G(r,\psi) \frac{f(l,r,n,q)}{e (\frac{r}{q}-\frac{l}{n} )-1} \ll& q^{1/2}\sum_{r=1}^{q-1} \frac{(r,q)}{\vert e (\frac{r}{q}-\frac{l}{n} )-1\vert } \\ \ll& q^{1/2}\sum_{r=1}^{q-1} \frac{(r,q)}{\vert \sin\pi (\frac{r}{q}-\frac{l}{n} )\vert } \ll q^{1/2}\sum_{r=1}^{q-1} \frac{(r,q)}{\langle \frac {r}{q}-\frac{l}{n}\rangle } \\ =&q^{1/2}\mathop{\mathop{\sum}_{d\mid q}}_{d< q} \mathop{\mathop{\sum }_{r\leqslant q-1}}_{(r,q)=d} \frac{d}{\langle \frac{r}{q}-\frac{l}{n}\rangle }=q^{1/2}\mathop {\mathop{\sum}_{d\mid q}}_{d< q}d \mathop{\mathop{\sum}_{m\leqslant\frac{q-1}{d}}}_{(m,q)=1}\frac {1}{\langle \frac{md}{q}-\frac{l}{n}\rangle } \\ =&q^{1/2}\mathop{\mathop{\sum}_{d\mid q}}_{d< q}d \sum_{k\mid q}\mu(k)\sum_{m\leqslant\frac{q-1}{kd}} \frac{1}{\langle \frac{mkd}{q}-\frac{l}{n}\rangle }. \end{aligned}$$
Now write \(\frac{k}{q/d}=\frac{h_{0}}{q_{0}}\), where \(q_{0}\geqslant 1\), \((h_{0},q_{0})=1\), we have \(\frac{q}{kd}=\frac{q_{0}}{h_{0}}\leqslant q_{0}\leqslant \frac{q}{d}\). Then Lemma 4 implies
$$\biggl\langle \frac{m_{i}kd}{q}-\frac{m_{j}kd}{q} \biggr\rangle = \biggl\langle \frac {(m_{i}-m_{j})h_{0}}{ q_{0}} \biggr\rangle \geqslant\frac{1}{q_{0}} \quad \text{if } i\neq j, 1\leqslant i, j\leqslant\frac{q-1}{kd}. $$
So we get
$$\begin{aligned} \sum_{r=1}^{q-1} G(r,\psi) \frac{f(l,r,n,q)}{e (\frac{r}{q}-\frac{l}{n} )-1} \ll &q^{1/2}\mathop{\mathop{\sum}_{d\mid q}}_{d< q}d \sum_{k\mid q}q_{0}\log \biggl( \frac{q-1}{kd}+1 \biggr) \\ \ll& q^{1/2}\mathop{\mathop{\sum}_{d\mid q}}_{d< q}d \sum_{k\mid q}\frac {q}{d}\log q \ll q^{3/2}d^{2}(q)\log q. \end{aligned}$$
(2.1)
Thus
$$\mathop{{\sum}'}_{a=1}^{q}\mathop{{ \sum}'}_{b=1}^{q}\chi_{1}(a) e \biggl(\frac{(a+b)l}{n} \biggr) \ll q^{1/2}\phi(q)d^{2}(q) \log q. $$
 □

3 Proof of the theorem

In this section, we shall complete the proof of the theorem.

Proof of the theorem

From the orthogonality relation for Dirichlet characters \(\bmod\ q\) and the trigonometric sum identity, we can get
$$\begin{aligned} \sum_{a\in\mathcal{C}(1,q)}\psi (a) =&\sum _{a=1}^{q}\psi(a)- \mathop{\mathop{\mathop{{\sum }}_{a=1}}_{n\mid(a+\overline {a})}}^{q}\psi(a) \\ =&\sum_{a=1}^{q}\psi(a)- \mathop{ \mathop{\mathop{{\sum}'}_{a=1}^{q} \mathop{{\sum }'}_{b=1}^{q}}_{n\mid(a+b)}}_{ab\equiv1(\bmod q)} \psi(a) \\ =&-\frac{1}{\phi(q)}\sum_{\chi\bmod q}\mathop{\mathop{{ \sum }'}_{a=1}^{q}\mathop{{\sum }'}_{b=1}^{q}}_{n\mid(a+b)}\psi(a)\chi (ab) \\ =&-\frac{1}{n\phi(q)}\sum_{\chi\bmod q}\mathop{{\sum }'}_{a=1}^{q}\mathop{{\sum }'}_{b=1}^{q} \psi(a)\chi(ab)\sum _{l=1}^{n}e \biggl(\frac{(a+b)l}{n} \biggr) \\ =&-\frac{1}{n\phi(q)}\mathop{\mathop{\sum_{\chi\bmod q}}_{\chi \neq\chi_{0}}}_{\chi\neq\overline{\psi}} \mathop{{\sum }'}_{a=1}^{q}\mathop{{ \sum }'}_{b=1}^{q} \psi(a)\chi(ab)\sum _{l=1}^{n}e \biggl(\frac{(a+b)l}{n} \biggr) \\ &{}-\frac{1}{n\phi(q)}\sum_{l=1}^{n} \mathop{{\sum }'}_{a=1}^{q}\mathop{{\sum }'}_{b=1}^{q} \psi(a)e \biggl( \frac{(a+b)l}{n} \biggr) \\ &{} -\frac{1}{n\phi(q)}\sum_{l=1}^{n} \mathop{{\sum}'}_{a=1}^{q}\mathop {{ \sum }'}_{b=1}^{q} \overline{\psi}(b)e \biggl(\frac{(a+b)l}{n} \biggr) \\ :=&-E_{1}-E_{2}-E_{3}. \end{aligned}$$
First of all, we shall estimate \(E_{1}\). Making use of Lemma 3, we get
$$\begin{aligned} E_{1} =&\frac{1}{n\phi(q)}\mathop{\mathop{\sum _{\chi\bmod q}}_{\chi\neq\chi_{0}}}_{\chi\neq\overline{\psi}}\mathop{{\sum }'}_{a=1}^{q}\mathop{{\sum}'}_{b=1}^{q} \psi(a)\chi(ab)\sum_{l=1}^{n}e \biggl( \frac{(a+b)l}{n} \biggr) \\ =&\frac{1}{n\phi(q)}\mathop{\mathop{\sum_{\chi\bmod q}}_{\chi\neq\chi_{0}}}_{\chi\neq\overline{\psi}} \sum_{l=1}^{n}\sum _{a=1}^{q}\chi\psi(a)e \biggl(\frac {al}{n} \biggr) \sum_{b=1}^{q}\chi(b)e \biggl( \frac{bl}{n} \biggr) \\ =&\frac{1}{n\phi(q)}\mathop{\mathop{\sum_{\chi\bmod q}}_{\chi\neq\chi_{0}}}_{\chi\neq\overline{\psi}} \sum_{l=1}^{n}\sum _{a=1}^{q}\frac{1}{q}\sum _{r_{1}=1}^{q-1}G(r_{1},\chi\psi) e \biggl(- \frac{ar_{1}}{q} \biggr)e \biggl(\frac{al}{n} \biggr) \\ &{} \times\sum_{b=1}^{q} \frac{1}{q} \sum_{r_{2}=1}^{q-1}G(r_{2}, \chi) e \biggl(-\frac{br_{2}}{q} \biggr)e \biggl(\frac{bl}{n} \biggr) \\ =&\frac{1}{n\phi(q)q^{2}}\mathop{\mathop{\sum_{\chi \bmod q}}_{\chi\neq\chi_{0}}}_{\chi\neq\overline{\psi}} \sum_{l=1}^{n}\sum _{r_{1}=1}^{q-1}G(r_{1},\chi\psi) \sum _{r_{2}=1}^{q-1}G(r_{2},\chi) \\ & {} \times\sum_{a=1}^{q}e \biggl( \biggl( \frac{l}{n}- \frac{r_{1}}{q} \biggr)a \biggr)\sum _{b=1}^{q}e \biggl( \biggl(\frac{l}{n}- \frac{r_{2}}{q} \biggr)b \biggr) \\ =&\frac{1}{n\phi(q)q^{2}}\sum_{l=1}^{n} \sum _{r_{1}=1}^{q-1}\sum_{r_{2}=1}^{q-1} \frac {f_{1}(l,r_{1},n,q)f_{2}(l,r_{2},n,q)}{ (e (\frac{l}{n}-\frac{r_{1}}{q} )-1 ) (e (\frac{l}{n}-\frac{r_{2}}{q} )-1 )} \\ &{} \times\mathop{\mathop{\sum_{\chi\bmod q}}_{\chi\neq\chi_{0}}}_{\chi\neq\overline{\psi}}G(r_{1}, \chi\psi)G(r_{2},\chi) \\ \ll&\frac{1}{\phi(q)q^{2}}\sum_{l=1}^{n} \sum_{r_{1}=1}^{q-1}\sum _{r_{2}=1}^{q-1}\frac {\phi(q)q^{1/2}(r_{1},q)^{1/2}(r_{2},q)^{1/2}d(q)}{ \vert e (\frac{l}{n}-\frac{r_{1}}{q} )-1\vert \vert e (\frac{l}{n}-\frac{r_{2}}{q} )-1\vert } \\ =&\frac{d(q)}{q^{3/2}}\sum_{l=1}^{n} \sum _{r_{1}=1}^{q-1}\sum_{r_{2}=1}^{q-1} \frac {(r_{1},q)^{1/2}(r_{2},q)^{1/2}}{ \vert e (\frac{l}{n}-\frac{r_{1}}{q} )-1\vert \vert e (\frac{l}{n}-\frac{r_{2}}{q} )-1\vert } \\ \ll&\frac{d(q)}{q^{3/2}}\sum_{l=1}^{n} \Biggl(\sum_{r=1}^{q-1}\frac{(r,q)^{1/2}}{ \vert e (\frac{l}{n}-\frac{r}{q} )-1\vert } \Biggr)^{2}. \end{aligned}$$
Similar to (2.1), we have
$$\sum_{r=1}^{q-1}\frac{(r,q)^{1/2}}{ \vert e (\frac{l}{n}-\frac{r}{q} )-1\vert } \ll \mathop{\mathop{\sum}_{d\mid q}}_{d< q}d^{1/2} \sum _{k\mid q}\frac {q}{d}\log q =q\log q\mathop{ \mathop{\sum}_{d\mid q}}_{d< q}d^{-1/2}\sum _{k\mid q}1 \ll qd^{2}(q)\log q. $$
Then
$$\begin{aligned} E_{1}\ll\frac{d(q)}{q^{3/2}}q^{2}d^{4}(q) \log ^{2}q=q^{1/2}d^{5}(q)\log^{2}q. \end{aligned}$$
(3.1)
Second, we estimate \(E_{2}\). By Lemma 5, we have
$$\begin{aligned} E_{2}\ll\frac{1}{\phi(q)}q^{1/2} \phi(q)d^{2}(q)\log q=q^{1/2}d^{2}(q)\log q. \end{aligned}$$
(3.2)
In the same way we can get the estimate
$$\begin{aligned} E_{3}\ll q^{1/2}d^{2}(q)\log q. \end{aligned}$$
(3.3)

Combining (3.1), (3.2), and (3.3), we obtain the result. □

Declarations

Acknowledgements

This work is supported by the National Natural Science Foundation of China (No. 11201275), the Natural Science Foundation of Shaanxi Province of China (No. 2016JM1017), the Scientific Research Program Funded by Shaanxi Provincial Education Department (No. 16JK1373) and the Fundamental Research Funds for the Central Universities (No. GK201503014). The authors want to express their great thanks to the anonymous referee for his/her helpful comments and suggestions. The first and the fourth authors also gratefully acknowledge the support, hospitality, and excellent conditions of the School of Computer Science and Engineering, School of Mathematics and Statistics of UNSW during their visits.

Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Authors’ Affiliations

(1)
School of Science, Xi’an Technological University
(2)
School of Mathematics and Information Science, Shaanxi Normal University

References

  1. Guy, RK: Unsolved Problems in Number Theory, pp. 139-141. Springer, New York (1981) View ArticleGoogle Scholar
  2. Zhang, WP: On a problem of D. H. Lehmer and its generalization. Compos. Math. 86(3), 307-316 (1993) MathSciNetMATHGoogle Scholar
  3. Zhang, WP: On a problem of D. H. Lehmer and its generalization (II). Compos. Math. 91(1), 47-56 (1994) MathSciNetMATHGoogle Scholar
  4. Lu, YM, Yi, Y: On the generalization of the D.H. Lehmer problem. Acta Math. Sin. (Engl. Ser.) 25(8), 1269-1274 (2009) MathSciNetView ArticleMATHGoogle Scholar
  5. Ma, R, Zhang, YL, Zhang, GH: On a kind of Dirichlet character. Abstr. Appl. Anal. 2013, Article ID 750964 (2013) MathSciNetGoogle Scholar
  6. Han, D, Zhang, WP: Upper bound estimate of character sums over Lehmer’s number. J. Inequal. Appl. 2013, 392 (2013) View ArticleMATHGoogle Scholar
  7. Xi, P, Yi, Y: On character sums over flat numbers. J. Number Theory 130(5), 1234-1240 (2010) MathSciNetView ArticleMATHGoogle Scholar
  8. Ren, GL, He, DD, Zhang, TP: On certain character sums. Quaest. Math. (to appear) Google Scholar
  9. Alkan, M, Simsek, Y: Generating function for q-Eulerian polynomials and their decomposition and applications. Fixed Point Theory Appl. 2013, 72 (2013) MathSciNetView ArticleMATHGoogle Scholar
  10. Shparlinski, IE: Open problems on exponential and character sums. In: Ser. Number Theory Appl., vol. 6, pp. 222-242. World Scientific, Hackensack, NJ (2010) Google Scholar
  11. Pan, CD, Pan, CB: Goldbach Conjecture. Science Press, Beijing (1981) MATHGoogle Scholar

Copyright

© Ma et al. 2016